2021
DOI: 10.1186/s12974-021-02283-z
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-resident M2 macrophages directly contact primary sensory neurons in the sensory ganglia after nerve injury

Abstract: Background Macrophages in the peripheral nervous system are key players in the repair of nerve tissue and the development of neuropathic pain due to peripheral nerve injury. However, there is a lack of information on the origin and morphological features of macrophages in sensory ganglia after peripheral nerve injury, unlike those in the brain and spinal cord. We analyzed the origin and morphological features of sensory ganglionic macrophages after nerve ligation or transection using wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…Since they express general cholesterol receptors, like LDLR and VLDLR, they would be capable of taking up cholesterol from the extracellular space, where it might be released from activated macrophages. Macrophages are known for their high cholesterol production, and we and others have shown that they increase in number and migrate into the SGC-neuron unit after injury 13, [53][54][55][56] . At present, however, this remains speculation until more functional data can be obtained.…”
Section: Discussionmentioning
confidence: 88%
“…Since they express general cholesterol receptors, like LDLR and VLDLR, they would be capable of taking up cholesterol from the extracellular space, where it might be released from activated macrophages. Macrophages are known for their high cholesterol production, and we and others have shown that they increase in number and migrate into the SGC-neuron unit after injury 13, [53][54][55][56] . At present, however, this remains speculation until more functional data can be obtained.…”
Section: Discussionmentioning
confidence: 88%
“…Since they express general cholesterol receptors, like LDLR and VLDLR, they would be capable of taking up cholesterol from the extracellular space, where it might be released from activated macrophages. Macrophages are known for their high cholesterol production, and we and others have shown that they increase in number and migrate into the SGCneuron unit after injury (Lu & Richardson, 1993;Dubový, Tučková, Jančálek, Svíženská, & Klusáková, 2007;Vega-Avelaira, Geranton, & Fitzgerald, 2009;Jager et al, 2020;Iwai et al, 2021). At present, however, this remains speculation until more functional data can be obtained.…”
Section: Discussionmentioning
confidence: 93%
“…As reported previously, polarized macrophages in the sensory ganglion can be detected by CD86 (marks M1 phenotype) and CD163 (marks M2 phenotype). 28 , 29 …”
Section: Resultsmentioning
confidence: 99%